Recurrent abdominal pain in adolescents with anxiety and depression disorders - Fastralina, Fastralina; Sofyani, Sri; Simbolon, M. Joesoef; Lubis, Iskandar Z. (Paediatrica Indonesiana, 2013)
Background Anxiety and depression disorders in adolescents may affect their academic performances and social functioning at school. Adolescents with these disorders sometimes develop recurrent abdominal pain (RAP). Objective To assess the occurence of recurrent abdominal pain among adolescents with anxiety and depression disorders Methods We conducted a cross-sectional study from August to September 2009 in 12-18 year-old adolescents from 3 junior high schools and 3 senior high schools in Secanggang Subdistrict, Langkat District, North Sumatera Province. We screened 960 adolescents. Subjects were selected by consecutive sampling and instructed to fill the child behavior checklist (CBCL) and children’s depression inventory (CDI) forms. Those with suspected anxiety/depression (CBCL score 2: 12 for boys and 2: 14 for girls) and those with suspected depression (CDI score 2: 13) were then examined by a psychiatrist. Adolescents diagnosed with anxiety or depression disorders were instructed to fill the RAP questionnaire based on Apley and Naish criteria. Results From the CBCL and CDI forms, 250 students were suspected of having anxiety and/or depression. From these, 144 students participated in this study. Of the 84 students with anxiety disorders, 60 (71.4%) students suffered from RAP. Of the 60 students with depression disorders, 31 (51 %) suffered from RAP. Conclusion Adolescents with anxiety or depression are more likely to have recurrent abdominal pain.